2001
DOI: 10.1104/pp.125.2.1126
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Maize Cytochrome P450 Monooxygenases Induced in Response to Safeners and Bacterial Pathogens

Abstract: Plants use a diverse array of cytochrome P450 monooxygenases in their biosynthetic and detoxification pathways. To determine the extent to which various maize P450s are induced in response to chemical inducers, such as naphthalic anhydride (NA), triasulfuron (T), phenobarbital, and bacterial pathogens (Erwinia stuartii, Acidovorax avenae), we have analyzed the response patterns of seven P450 transcripts after treatment of seedlings with these inducers. Each of these P450 transcripts has distinct developmental,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 42 publications
2
53
0
2
Order By: Relevance
“…In all cases, the induction profile was found to be specific for a particular CYP or subset of CYPs and not the result of a global induction of CYP genes. Analyzing the response pattern of seven CYP transcripts after treatment of maize seedlings with chemical inducers, Persans et al (2001) These findings demonstrate that the pattern of CYP regulation is strictly correlated to their biological function. Following this line of argument, the CYP87A3 gene product might be placed in the tuning of growth responses.…”
Section: Discussion Cyp: From Regulation To Functionmentioning
confidence: 99%
“…In all cases, the induction profile was found to be specific for a particular CYP or subset of CYPs and not the result of a global induction of CYP genes. Analyzing the response pattern of seven CYP transcripts after treatment of maize seedlings with chemical inducers, Persans et al (2001) These findings demonstrate that the pattern of CYP regulation is strictly correlated to their biological function. Following this line of argument, the CYP87A3 gene product might be placed in the tuning of growth responses.…”
Section: Discussion Cyp: From Regulation To Functionmentioning
confidence: 99%
“…The most important enzymes involved in are Cytochrome P450 monooxygenases (P450s) (Eerd et al, 2003;Yuan et al, 2007), which are membrane-bound haem proteins that catalyze oxy-reduction reactions of endogenous and xenobiotic substrates (Bolwell et al, 1994;Persans et al, 2001;Hatzios & Burgos, 2004;Edwards et al, 2005). In fact, Cytochromes P450 are a large family of enzymes responsible for the addition of a single atom of oxygen to hydrophobic substrates (Bolwell et al, 1994;Preston, 2004).…”
Section: Herbicide Metabolismmentioning
confidence: 99%
“…Previous studies have confirmed that CYP450 and GST enzymes play the key roles in the hydroxylation and reduction of xenobiotics such as PCBs and triazine, and CYP71C3v2 and GST31 are the most important CYP450 and GST isozymes in maize, respectively. 36,37 Therefore, the 3-D structures of CYP71C3v2 and GST31 isozymes were used for homology modeling. The primary sequences of CYP71C3v2 and GST31 are available at the National Center for Biotechnology Information (NCBI) Web site (http://www.ncbi.nlm.nih.gov).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%